2018
DOI: 10.1103/physreva.97.022337
|View full text |Cite
|
Sign up to set email alerts
|

Improved quantum backtracking algorithms using effective resistance estimates

Abstract: We investigate quantum backtracking algorithms of the type introduced by Montanaro (arXiv:1509.02374). These algorithms explore trees of unknown structure and in certain settings exponentially outperform their classical counterparts. Some of the previous work focused on obtaining a quantum advantage for trees in which a unique marked vertex is promised to exist. We remove this restriction by recharacterising the problem in terms of the effective resistance of the search space. In this paper, we present a gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Ambainis and Kokainis [6] showed that the quantum runtime bound can be improved to O( √ T n 3/2 ), where T is the number of nodes actually explored by the classical algorithm. Second, Jarret and Wan [60] showed that the runtime of Theorem 2 can be improved to O( √ T n) without the need for any promise on the uniqueness of the solution 6 . Also, the quantum backtracking algorithm has been applied to exact satisfability problems [69], the Travelling Salesman Problem [77], and attacking lattice-based cryptosystems [5,81].…”
Section: For Each W ∈ [K]mentioning
confidence: 99%
“…Ambainis and Kokainis [6] showed that the quantum runtime bound can be improved to O( √ T n 3/2 ), where T is the number of nodes actually explored by the classical algorithm. Second, Jarret and Wan [60] showed that the runtime of Theorem 2 can be improved to O( √ T n) without the need for any promise on the uniqueness of the solution 6 . Also, the quantum backtracking algorithm has been applied to exact satisfability problems [69], the Travelling Salesman Problem [77], and attacking lattice-based cryptosystems [5,81].…”
Section: For Each W ∈ [K]mentioning
confidence: 99%
“…The latter, in a similar fashion to this work, uses quantum search to accelerate the subroutines of the simplex method (e.g., variable pricing). There also exist recent efforts to use algorithms based on quantum search and phase estimation to speed up tree search methods including branch-and-bound [46] and backtracking search [15,16,47]; we discuss the latter in more detail in Section 6. See in particular [15, Sec.…”
Section: Related Workmentioning
confidence: 99%
“…These smaller subproblems require fewer resources, making them promising candidates for the early faulttolerant quantum computers of the future. With respect to search, we investigate the adaptation of existing quantum tree search algorithms [15,16] to the search performed within CP, and provide preliminary resource estimates for this integration. Our adaptations are focused on incorporating quantum filtering within both classical and quantum backtracking search algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be possible to improve the depth dependence by a factor of up to d, e.g. by extending ideas of [23].…”
Section: Return "No Solution"mentioning
confidence: 99%
“…• If the tree does not contain any marked nodes, the algorithm returns "not found". Jarret and Wan have described an algorithm [23] which solves the same tree search problem with complexity bounded by O( √ T d log 4 (md) log(m/ )), where m is the number of marked nodes. This is an improvement on (1) by up to a factor of almost d when m is small.…”
mentioning
confidence: 99%